Spin-resolved single-atom imaging of 6Li in free space - Bergschneider, Andrea; Klinkhamer, Vincent M.; Becher, Jan Hendrik Willibald; Klemt, Ralf; Zürn, Gerhard; Preiss, Philipp; Jochim, Selim (Physical review, 2018)
We present a versatile imaging scheme for fermionic 6Li atoms with single-particle sensitivity. Our method works for freely propagating particles and completely eliminates the need for confining potentials during the imaging process. We illuminate individual atoms in free space with resonant light and collect their fluorescence on an electron-multiplying CCD camera using a high-numerical-aperture imaging system. We detect approximately 20 photons per atom during an exposure of 20μs and identify individual atoms with a fidelity of (99.4±0.3)%. By addressing different optical transitions during two exposures in rapid succession, we additionally resolve the hyperfine spin state of each particle. The position uncertainty of the imaging scheme is 4.0μm, given by the diffusive motion of the particles during the imaging pulse. The absence of confining potentials enables readout procedures such as the measurement of single-particle momenta in time of flight, which we demonstrate here. Our imaging scheme is technically simple and easily adapted to other atomic species.
Gesehen am 09.07.2019
Im Titel ist die 6 in 6Li hochgestellt